IN VITRO EVALUATION OF ACECLOFENAC MONOLITHIC OSMOTIC PUMP TABLETS CONTAINING A SWELLABLE POLYMER - (:unkn) unknown (POLSKIE TOWARZYSTWO FARMACEUTYCZNE, 2018)
In this study, monolithic osmotic pump tablets which contain a swellable polymer and involve a RCS Class II nonsteroidal anti-inflammatory drug (NSAID). aceclofenac, have been generated and studied. Aceclofenac is mainly used for the relief of pain and inflammation in osteoarthritis, rheumatoid arthritis and ankylosing spondylitis; however. there are also several studies in the literature about the effectiveness of aceclofenac on colon cancer as well as other NSAIDs. In this present study, eight batches were produced using five different core tablet compositions, three different semipermeable membrane compositions. and having two different orifice sizes. The physical properties and in-viuo dissolution profiles of the generated formulations were examined and evaluated both in 0.1 M HCl and in pH 6.8 phosphate buffer. The effect of the orifice diameter size, molecular weight of polyoxyethylene, thickness of the semipermeable membrane, and coating solvent were observed. Drug releases from all formulations showed approximately zero order kinetics. Observed regression coefficients (r(2)) were found between 0.965 - 0.997 for zero order kinetics and maximum cumulative drug release was observed as 42.2% +/- 0.6 at 48 hours. Maximum drug release of up to 2.7% +/- 0.5 within the first six hours in dissolution tests showed that our monolithic osmotic pump tablets containing a swellable polymer were promising for oral colon-specific drug delivery.
Keywords: aceclofenac; osmotic pump; polyoxyethylene; ethyl cellulose; aqueous coating; CONTROLLED-RELEASE TABLET; DELIVERY; SYSTEM; PREDICTION; DRUGS